2015
DOI: 10.1016/j.celrep.2015.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Principles Governing A-to-I RNA Editing in the Breast Cancer Transcriptome

Abstract: SummaryLittle is known about how RNA editing operates in cancer. Transcriptome analysis of 68 normal and cancerous breast tissues revealed that the editing enzyme ADAR acts uniformly, on the same loci, across tissues. In controlled ADAR expression experiments, the editing frequency increased at all loci with ADAR expression levels according to the logistic model. Loci-specific “editabilities,” i.e., propensities to be edited by ADAR, were quantifiable by fitting the logistic function to dose-response data. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
157
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(173 citation statements)
references
References 58 publications
15
157
1
Order By: Relevance
“…10 ADAR1 regulates the editing frequency and number of edited sites. [6][7][8] ADAR1 mRNA expression is significantly positively correlated with the RNA editing level. 7 RNA sequencing analysis has revealed that ADAR1 is among the top 5% of upregulated genes in relapsed lobular breast cancer.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…10 ADAR1 regulates the editing frequency and number of edited sites. [6][7][8] ADAR1 mRNA expression is significantly positively correlated with the RNA editing level. 7 RNA sequencing analysis has revealed that ADAR1 is among the top 5% of upregulated genes in relapsed lobular breast cancer.…”
Section: Introductionmentioning
confidence: 93%
“…Cellular functions and regulations can be altered by A-to-I editing through changes in messenger RNA (mRNA) splicing, stability, localisation and translation as well as interference with the binding of regulatory RNAs. 7 With the improvement in sequencing and analysis technologies, researchers have studied RNA editing events using RNA sequencing data. [6][7][8][9] In humans, the ADAR family comprises ADAR1, ADAR2 and ADAR3, which share repeated copies of dsRNA-binding domains and a catalytic adenosine deaminase domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 RNA editing is globally controlled by tumor interferon and adenosine deaminase acting on RNA (ADAR) copy number, and both factors are highly prevalent among human cancers. 11,12 The high frequency of a site-specific RNA editing event, which is the serine-toglycine substitution at residue 367 (S367G) in antizyme inhibitor 1 (AZIN1), was uncovered in hepatocellular and esophageal carcinoma. 13,14 Here, we illustrated how AZIN1 RNA editing occurred in NSCLC patients' specimens and cell line models as well as demonstrated the role of ADARmediated AZIN1 RNA editing in NSCLC development.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have characterized the critical role of individual missense A-to-I RNA editing events in cancer development (Chen et al 2013;Galeano et al 2013;Han et al 2014). More recently, we and other groups have systematically characterized the RNA-editing genomic landscape in various cancer types using mRNA-seq data from The Cancer Genome Atlas (TCGA) (Fumagalli et al 2015;Han et al 2015;Paz-Yaacov et al 2015). These studies revealed a large number of dysregulated A-to-I RNA editing events in tumor samples relative to normal samples, many of which show clinically relevant patterns and suggested that, like "driver" somatic mutations, RNA editing events alter the growth of cancer cells and also selectively change drug sensitivity in cell lines consistent with therapeutic relevance in patients.…”
mentioning
confidence: 99%